Online authentication using smart card technology in mobile phone infrastructure - Mantoro, Teddy; Milisic, Admir; Ayu, Media Anugerah (IGI Global, 2011)
The widespread of Internet usage has resulted in a greater number and variety of applications involving different types of private information. In order to diminish privacy concerns and strengthen user trust, security improvements in terms of authentication are necessary. The solutions need to be convenient, entailing ease of use and higher mobility. The suggested approach is to make use of the already popular mobile phone and to involve the mobile network, benefiting from Subscriber Identity Module (SIM) card’s tamper resistance to become trusted entities guarding personal information and identifying users. Mobile phone’s SIM card is convenient for safely storing security parameters essential for secured communication. It becomes secure entity compulsory for getting access to privacy sensitive Internet applications, like those involving money transfers. Utilizing the NFC interface passes the personal user keys only when needed, giving additional strength to the traditional public key cryptography approach in terms of security and portability.